Pengaruh Motivasi, Disiplin Kerja dan Budaya Kerja terhadap Kinerja Pegawai: Studi pada Kantor Kecamatan Cikoneng dan Desa Se-Kecamatan Cikoneng Kabupaten Ciamis - Lilis Ratnawati; Nurdiana Mulyantini; Nana Darna (Jurnal Manajemen Bisnis Era Digital, 2024)
The problems faced in this study include (1) How does motivation affect employee performance at the Cikoneng District Office and Villages in Cikoneng District, Ciamis Regency? (2) How does work discipline affect employee performance at the Cikoneng District Office and Villages in Cikoneng District, Ciamis Regency? (3) How does work culture affect employee performance at the Cikoneng District Office and Villages in Cikoneng District, Ciamis Regency? (4) How do motivation, work discipline and work culture affect employee performance at the Cikoneng District Office and Villages in Cikoneng District, Ciamis Regency? This study aims to study, find out, and analyze (1) The effect of motivation on employee performance at the Cikoneng District Office and Villages in Cikoneng District, Ciamis Regency. (2) The effect of work discipline on employee performance at the Cikoneng District Office and Villages in Cikoneng District, Ciamis Regency. (3) The influence of work culture on employee performance at the Cikoneng District Office and Villages in Cikoneng District, Ciamis Regency. (4) The influence of motivation, work discipline and work culture on employee performance at the Cikoneng District Office and Villages in Cikoneng District, Ciamis Regency. The results of the study inform that (1) Motivation has a positive influence on employee performance at the Cikoneng District Office and Villages in Cikoneng District, Ciamis Regency. (2) Work discipline has a positive influence on employee performance at the Cikoneng District Office and Villages in Cikoneng District, Ciamis Regency. (3) Work culture has a positive influence on employee performance at the Cikoneng District Office and Villages in Cikoneng District, Ciamis Regency. (4) Motivation, work discipline and work culture have a positive influence on employee performance at the Cikoneng District Office and Villages in Cikoneng District, Ciamis Regency.